Analisis Kinerja Keuangan Pada PT Pelayaran Tonasa Lines - Alief Kirana Ramdhana, Muh; Sahade; Nurafiah (PROGRAM STUDI AKUNTANSI SYARIAH FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2025)
This study aims to (1) Analyze how the financial performance of PT Pelayaran Tonasa Lines in 2021-2023 is based on the industry average ratio standard. (2) Analyze how the financial performance of PT Pelayaran Tonasa Lines in 2021-2023 is based on the Decree of the Minister of BUMN No. KEP 100/MBU/2002. There are four variables in this study, namely the liquidity ratio, activity ratio, profitability ratio and solvency ratio. The population in this study is the financial report of PT Pelayaran Tonasa Lines and the sample is in the form of the balance sheet and profit and loss report of PT. Pelayaran Tonasa Lines for the period 2021-2023. The data collection technique used is documentation which includes secondary data. The data analysis technique used in this study is quantitative descriptive.The results of this study show that based on industry standards, the current ratio has increased from year to year, but has only been able to exceed the industry standard in 2023, which is 229%, indicating that the company is increasingly able to meet its short-term obligations. Likewise, equity to assets is able to exceed the industry standard, which is 39% in 2021 to 2023, indicating that the company relies more on equity than debt. However, the total asset turnover ratio (TATO) and Return on Equity (ROE) from 2021 to 2023 are still below the industry average, indicating that operational efficiency and profitability still need to be improved. Meanwhile, in terms of assessment based on the Decree of the Minister of SOEs, the company's assessment score has increased from 67.85% (category A) in 2021, to 83.92% (category AA) in 2022, and reached 89.28% (category AA) in 2023. This reflects an increase in the company's financial health which is quite good or healthy according to SOE standards.